NR3C1 variants and glucocorticoid response in childhood nephrotic syndrome in North India - Sarranya Paranthaman; Priyanka Srivastava; Anu Kumari; Chitra Bhardwaj; Pratibha Bawa; Anupriya Kaur; Inusha Panigrahi; Lesa Dawman; Karalanglin Tiewsoh (BMC Nephrology)
Abstract Background Nephrotic syndrome (NS) is a common kidney disorder in children, characterized by significant proteinuria, hypoalbuminemia, and peripheral edema. While glucocorticoids (GCs) are the first-line treatment for pediatric nephrotic syndrome (NS), a subset of patients exhibit steroid resistance, leading to poor prognosis and a higher risk of long-term kidney damage. The glucocorticoid receptor gene (NR3C1) plays a pivotal role in mediating the effects of GCs, and its polymorphisms have been implicated in variable GC responses. Methods This study investigates the association between NR3C1 single nucleotide polymorphisms (SNPs) (rs6877893 and rs10482634) in 50 patients with steroid-sensitive nephrotic syndrome (SSNS) and 50 steroid-resistant nephrotic syndrome (SRNS) individuals by Kompetitive Allele Specific Polymerase Chain Reaction (KASP) assay and altered GC receptors (GRα and GRβ) expression by Real-Time PCR (RT-PCR). Adverse effect of steroid therapy was also assessed. Results Genotyping revealed a significant association between GG genotype of SNP rs10482634 and steroid resistance, suggesting that it may contribute to the heterogeneity in GC response in this population. There is also a positive association of AA genotype of rs10482634 with short stature and AG genotype of rs10482634 with cushingoid habitus, as a side effect of steroid therapy. We have also found an enhanced expression of GRα in SSNS population. No significant association was found between the SNP rs6877893 and the response to steroid treatment in the study cohort. Our study revealed higher rates of drug-related complications in patients receiving larger cumulative doses of steroids. Conclusion These findings highlight the importance of genetic screening of NR3C1 SNPs in predicting steroid responsiveness and tailoring personalized therapeutic strategies in pediatric NS. Clinical trial number not applicable.